(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
The bryophyte flora of the Cheremys’ky nature reserve (the Volyns’ka oblast’, NW Ukraine) includes 114 species of 67 genera, 42 families belonging to two divisions: Marchantiophyta (12 spp.) and Bryophyta (102 spp.). Among them, glacial relicts (Calliergon trifarium, Scorpidium scorpioides, Helodium blandowii) and rare taxa (Orthotrichum lyellii, Aulacomnium androgynum, Thuidium tamariscinum) are presented.